Better fisheries management can help reduce conflict, improve food security, and increase economic productivity in the face of climate change. (October 2019) - Burden, Merrick; Fujita, Rod
Abstract: Fisheries provide food for billions of people and employ tens of millions. Climate change is already causing changes in the distribution and abundance of many of the fish stocks that support fisheries, resulting in overfishing and conflicts arising from changes in access to fisheries and in the distribution of fishery benefits. If business continues as usual, these problems will likely get worse, with 80% of the worlds stocks falling into an overfished status by the middle of the next decade. This does not have to be the case. Many fishery challenges posed by climate change, such as changes in stock abundance and distribution, are familiar. Fisheries have developed effective ways to address them, such as harvest control rules that vary with climate regime, frequent monitoring, and adaptive management systems. However, many of these approaches are not yet widespread. Indeed more than 80% of the world's catch is derived from stocks without a formal stock assessment, which makes implementation of robust forms of management problematic. Moreover, climate change is introducing new kinds of challenges, such as the introduction of new species into fisheries. A great deal of political will, capacity building, and collective action will be necessary to scale fisheries management that is responsive and adaptive to climate change. If this can be accomplished, recent projections suggest that many fisheries could continue to produce good yields and rebuild depleted stocks even in the face of moderate climate change.